Islamic Tasawwuf: It's Relevance & Role in Resolving Conflict Resolution - Muneeb Ahmad; Afroz Ahmad Bisati (International Journal of Emerging Issues in Islamic Studies, 2023)
The most insisting aspect of the Islam is that it constantly urges mankind to realize the actions close to the creator. Islamic teachings frequently remind humanity of the primordial covenant which took place between God and Humanity wherein the souls of human beings categorically witnessed that God is our Lord. In fact, it was a covenant of future relationship between God and Humanity. Islamic Tasawwuf being a spiritual mechanism which aims to fulfill this covenant. It is an attempt to bring the creation close to its creator (Allah). Islamic Tasawwuf is an integral and integrated element of the socio-religious aspect of the Muslim in modern times, where, although the scientific and technological developments are contributing a lot towards providing a considerable amount of amenities for human beings, however, spiritual crisis is on of the grave issues confronting by the human beings in modern times, consequently there is an imbalance between spirituality and mundane concerns of the Humanity. Therefore, Islamic Tasawwuf can play a paramount role in pulling out the humanity from the spiritual crisis and it can also espouse the society in terms of spiritual development. Islamic Tasawwuf can maintain a balance between mundane needs and spirituality. Similarly, taking into account the phenomenon of inter faith dialogue, especially in the contemporary world which presents a heterogeneous picture, Islamic Tasawwuf is of inestimable importance. Because of its peaceful nature, Islamic Tasawwuf can be an effective tool for the inter faith besides the moral and the social up gradation of the Humanity. Islamic Tasawwuf is a prerequisite with realization, ethics and human service, is the only possible solution to the issues confronting by the modern societies, and has legitimacy in  Islamic teachings. The Sufi heritage of Islam actually manifest in contemporary societies. Therefore, in this paper my venture is directed to highlight the key features of Islamic Tasawwuf and its manifestations and relevance in the contemporary times.